2019
DOI: 10.1590/1516-4446-2018-0246
|View full text |Cite
|
Sign up to set email alerts
|

Bullying among adolescents: are the victims also perpetrators?

Abstract: Objective:To analyze factors associated with the prevalence of maltreatment and bullying and to identify types of involvement (verbal, physical, social, sexual, cyberbullying) among high school students aged 15 to 19 years.Methods:A cross-sectional, school-based epidemiological survey was performed. The sample included 2,293 adolescents from public and private schools in the Greater Vitoria area (state of Espírito Santo, Brazil). A modified version of the Brazilian Portuguese Olweus Bully/Victim Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
0
12
0
6
Order By: Relevance
“…The sample is also not representative of all children and youths as the participants are in-school with context that differs from that of out-of-school children and adolescents. In addition, although the type of school [73] and body images and size [74] could result in bullying, we did not include this in the data analysis: data on type of school was not available in the primary data. Nonetheless, the study generated several hypotheses that can lead to further research on the inter-relationship between psychosocial factors, culture and oral health.…”
Section: Discussionmentioning
confidence: 99%
“…The sample is also not representative of all children and youths as the participants are in-school with context that differs from that of out-of-school children and adolescents. In addition, although the type of school [73] and body images and size [74] could result in bullying, we did not include this in the data analysis: data on type of school was not available in the primary data. Nonetheless, the study generated several hypotheses that can lead to further research on the inter-relationship between psychosocial factors, culture and oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evidence suggesting that these variables prevent interpersonal aggression [ 37 , 44 , 59 , 72 , 74 ], limited studies have explored positive personal characteristics associated with bullying behavior. Moreover, although a considerable body of research has studied variables that influence bullying behavior [ 96 , 97 , 98 ], less attention has been paid to effects of these variables on both proactive and reactive aggression. Additionally, the moderated role of gender and age in the relationships between variables included in the study and both types of aggression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study found that children in school aggression status had an approximately 90% probability of reporting ever teasing or saying mean things to classmates and had a more than 50% probability of reporting ever pushing, kicking, or hitting classmates. Other studies also indicated that the most frequent type of school aggression was verbal bullying (Reisen et al, 2019; Wang et al, 2009). In addition, this study was consistent with a prior study (Pan et al, 2017) finding that most children were in the “None” violence status, and that children in this status tended to remain so when moving to higher grades, whereas the chances of remaining in cyber‐aggression and school aggression were relatively low for both boys and girls.…”
Section: Discussionmentioning
confidence: 93%